2018
DOI: 10.18632/oncotarget.26000
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of copy number variations and point mutations in BRCA1/2 genes using a single workflow by ion semiconductor sequencing pipeline

Abstract: Molecular analysis of BRCA1 (MIM# 604370) and BRCA2 (MIM #600185) genes is essential for familial breast and ovarian cancer prevention and treatment. An efficient, rapid, cost-effective accurate strategy for the detection of pathogenic variants is crucial. Mutations detection of BRCA1/2 genes includes screening for single nucleotide variants (SNVs), small insertions or deletions (indels), and Copy Number Variations (CNVs). Sanger sequencing is unable to identify CNVs and therefore Multiplex Ligation Probe ampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Copy number variation in both genes was reported by Wen-Ming Cao et al [ 35 ] with a percentage of 16.1% (5/31). While, other studies state that BRCA1/2 CNVs for HBOC patients is rarely found [ 64 , 65 ]. More global studies are required to define the implication of BRCA1/2 CNVs in HBOC.…”
Section: Discussionmentioning
confidence: 99%
“…Copy number variation in both genes was reported by Wen-Ming Cao et al [ 35 ] with a percentage of 16.1% (5/31). While, other studies state that BRCA1/2 CNVs for HBOC patients is rarely found [ 64 , 65 ]. More global studies are required to define the implication of BRCA1/2 CNVs in HBOC.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic CNVs are more frequent in BRCA1 than BRCA2 and reach respectively 27% and 8% of BRCA genetic variations. This may be explained by the higher number of Alu sequences in BRCA1 , and also by the homologous recombination events that occur between BRCA1 and its pseudogene [ 10 , 11 ]. The highest contribution of BRCA1 CNVs was reported in the Dutch population in which 27% to 36% of all germline BRCA1 mutations are CNVs [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The advent of NGS technologies made it possible to perform multi-gene massive sequencing, with very sensitive detection of gene variants, even complex, and copy number variations as well [62,63]. Several works [64][65][66][67] demonstrated the advantage of using NGS with respect to traditional methods for BRCA variant identification in terms of sensitivity, cost and time reduction. Importantly, the latter is very relevant for therapy decision-making, in consideration of the possible use of anti-PARP drugs for ovarian and breast cancer treatment [68][69][70].…”
Section: Ngs Applications For Brca1/2 Gene Analysismentioning
confidence: 99%
“…Some reports [66,79,80] described simultaneous NGS sequencing data collection and identification of BRCA rearrangements, simply by evaluating the presence of copy number variations (CNVs). This provides a fast and useful global first-step analysis that leads to more in-depth confirmatory investigation on positive samples by complementary tests, such as MLPA.…”
Section: Ngs Applications For Brca1/2 Gene Analysismentioning
confidence: 99%